Dietary supplementation with proanthocyanidins and rutin alleviates the symptoms of type 2 diabetes mice and regulates gut microbiota - Gao, Yue; Huang, Binbin; Qin, Yunyi; Qiao, Bing; Ren, Mengfei; Cao, Liqing; Zhang, Yan; Han, Maozhen (Frontiers in Microbiology, 2025)
BackgroundObesity and high fasting blood glucose (FBG) resulting from high-fat diets (HFDs) have emerged as significant public health concerns, garnering increasing attention. Recently, gut microbiota has been linked with metabolic diseases such as type 2 diabetes (T2DM), and its mediating role in dietary supplements has been confirmed. Seeking various dietary supplements to lose body weight (BW) and decrease FBG and explaining the underlying mechanism have become the research hotspots in T2DM studies.MethodsIn this study, rutin and proanthocyanidins (PA) were selected as dietary supplements (200 mg/kg × day, oral gavage, 6 weeks) in T2DM mice induced with HFD to assess their efficacy in weight loss, FBG reduction, gut microbiota alterations, and the associated underlying mechanisms.ResultsOur findings indicate that rutin was more effective than PA in relieving inflammation and fat hypertrophy, although both significantly reduced BW and FBG within 2 weeks after the intervention. Analysis of 16S rRNA amplicons revealed substantial alterations in the gut microbial community composition of mice administered with PA and rutin compared to HFD-fed mice. Importantly, several core microbes, particularly a series of probiotics, such as Akkermansia, Lactococcus, Odoribacter, Faecalibaculum, and Roseburia were identified, which were significantly correlated with the changes in BW and FBG.ConclusionOverall, our study highlights that rutin and PA can reduce BW, FBG, and inflammation by modulating the gut microbiota composition, providing novel perspectives for managing and treating weight and FBG concerns in obesity and T2DM patients through dietary supplements in clinical treatment.